KNOWLEDGE OF THE SUPERVISORS IN PIBID: TRAINING AND PARTNERSHIP - Chaluh, Laura Noemi [UNESP]; Martins, Betsamar Scopinho; Ramos de Azevedo, Maria Antonia [UNESP]; Osti, Andreia [UNESP] (Univ Metodista Piracicaba-unimep, 2017)
We discuss, in this paper, the place of the supervising teacher in Pibid-Programa Institucional de Infcio a Doccncia (Institutional Program of Initiation to Teaching). It is responsible for monitoring and supervising the activities of the initiation to teaching scholars at school. We problematize what knowledge the supervisor teacher needs from: (written recorded in the collective book by the supervisor teacher and the scholars, b) individual reports of scholars that deal with the contribution of the supervising teacher in the process of teacher training. We believe that the initial training of the scholars in school is favored by the educational practices of Pibid supervisor.
Keywords: PIBID; SUPERVISOR; KNOWLEDGE; SCHOOL-UNIVERSITY